Effect of adding Schroth physiotherapeutic scoliosis specific exercises to standard care in adolescents with idiopathic scoliosis on posture assessed using surface topography: A secondary analysis of a Randomized Controlled Trial (RCT) - Mohamed, Nada; Acharya, Vivechana; Schreiber, Sanja; Parent, Eric C.; Westover, Lindsey (PLOS ONE, 2024)
Background Adolescent idiopathic scoliosis (AIS) is a three-dimensional structural asymmetry of the spine and trunk affecting 2–4% of adolescents. Standard treatment is observation, bracing, and surgery for small, moderate, and large curves, respectively. Schroth exercises aim to correct posture and reduce curve progression. Purpose This study aimed to determine the effect of Schroth exercises added to the standard care compared to standard care alone on torso asymmetry in AIS. Methods In a randomized controlled trial (NCT01610908), 124 participants with AIS (age: 10–18, Cobb: 10°-45°, Risser: ≤3) were randomly assigned to the control (Standard care only) or Schroth (Standard care + Schroth treatment) group. Schroth treatment consisted of 1-hour weekly supervised sessions and 30–45 minutes of daily home exercises for six months. The control group received Schroth exercises in the last six months of the 1-year monitoring period. Markerless 3D surface topography assessed torso asymmetry measured by maximum deviation (MaxDev) and root mean square (RMS). Intention to treat linear mixed effects model analysis was compared to the per protocol analysis. Results In the intention to treat analysis, the Schroth group (n = 63) had significantly larger decreased RMS (-1.2 mm, 95%CI [-1.5,-0.9]mm, p = 0.012) and MaxDev (-1.9mm, 95%CI [-2.4,-1.5]mm, p = 0.025) measurements compared to controls (n = 57) after six months of intervention. In the per protocol analysis (Schroth n = 39, control n = 36), the Schroth group also had a significantly larger decrease compared to the control in both the RMS (-1.0mm, 95%CI [-1.9, -0.2]mm, p = 0.013) and MaxDev measurements (-2.0mm, 95%CI [-3.3,-0.5]mm, p = 0.037). For the control group, both the intention to treat and per protocol analysis showed no difference in RMS and MaxDev in the last six months of Schroth intervention (p>0.5). Conclusion Schroth Exercise treatment added to standard care (observation or bracing) reduced asymmetry measurements in AIS. As expected, a greater effect was observed for participants who followed the prescribed exercise treatment per protocol.